Proses fonologis bahasa Jawa: Kajian teori optimalitas - Subiyanto, Agus (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This paper aims to discuss phonological processes in Javanese, which are phonologically and syntactically conditioned. By using the Optimality Theory (OT), the relation between the input (phonemic form) and the output (phonetic form) involved in phonological processes will be explained. The data used in this paper are taken from a Javanese native speaker of Semarang dialect. In addition, this paper also used intuitive data from the writer, who is also a Javanese native speaker of Semarang dialect. The result of the analysis shows that OT is relevant to explain the phonological processes in Javanese such as a deletion of voiceless obstruents, a deletion of weak vowel [ə], an addition of weak vowel [ə], and an insertion of nasal.